2007
DOI: 10.1007/bf03026795
|View full text |Cite
|
Sign up to set email alerts
|

Modification de l’index bispectral suite à une embolisation avec alcool absolu chez un patient souffrant de malformation artérioveineuse intracrânienne

Abstract: Purpose:We report a case of bispectral index (BIS) falling to zero during absolute alcohol embolization of an intracranial arteriovenous malformation (AVM) under anesthesia. This case highlights the unusual effect of a therapeutic dose of parenteral alcohol on the central nervous system using BIS monitoring. Clinical features:A 29-yr-old male with a left parieto-occipital arteriovenous malformation underwent neuroendovascular embolization under general anesthesia. During injection of absolute alcohol injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Ethanol is usually injected with some form of ow arrest to limit egress from the malformation due to its propensity to cause various side effects after systemic absorption. [4][5][6][7][8][9] Yakes et al reported a complication rate of 10-30% related to alcohol. 10 The dose of ethanol used for ablation is the sole determinant of occurrence of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol is usually injected with some form of ow arrest to limit egress from the malformation due to its propensity to cause various side effects after systemic absorption. [4][5][6][7][8][9] Yakes et al reported a complication rate of 10-30% related to alcohol. 10 The dose of ethanol used for ablation is the sole determinant of occurrence of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…These include rupture of cerebral aneurysms during coiling 1 , embolization of arterio-venous malformations 2 and intraventricular haemorrhage during third ventriculoscopy 3 . Rapid increases in intracranial pressure and vasospasm have been postulated as possible causes for the decrease in BIS values.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was followed by external carotid arterial angiography, placing an Excelsior ® SL-10 microcatheter (Target Therapeutics/Boston Scientific, Fremont, CA, USA) under fluoroscopic guidance and placing a Traxcess ® 14 microguidewire (MicroVention, Tustin, CA, USA) into the trunk of middle meningeal artery followed by slow injection of absolute alcohol through the microcatheter for embolization ( 23 , 24 ). Based on previous reports and our experience using absolute alcohol in our institution ( 25 , 26 ), we mixed alcohol and contrast agent in an 8:2 ratios and used a dose of 0.03 ml/kg mixture for embolization, which we injected slowly. After injection, we removed the syringe and evaluated the extent of embolization.…”
Section: Methodsmentioning
confidence: 99%